Religious extremism? It is normal... - Bezniuk, Dmitry K. (Journal of the Belarusian State University. Sociology, 2019)
The reasons for the rise and spread of religious extremism are considered. The options for explaining the relationship between religious extremism and politics are analyzed in this article. An attempt is made to reveal the confessional specificity of the radicalization of religious life in the context of political and economic processes in modern society. The ways to overcome the radicalization of religion are proposed.